Automatic code generation using unified modeling language activity and sequence models. Issue 6 (1st December 2016) - Viswanathan, Sunitha Edacheril; Samuel, Philip
Abstract : A fully automatic translation of unified modeling language (UML) models to complete source code is not reported so far because some implementation details will not be there in the model, or a single UML model is not enough for complete code generation, or some model elements may not be directly convertible to source code. These issues are addressed in this study. The authors take workflow modelling and automation as the focus of their research. Hence, UML activity diagram is considered. Activity diagram alone cannot give the implementation details like object interactions. A formal association is found between activity and sequence diagrams to add object interaction details to the work flow. Moreover, the authors formulate an algorithm, Am_To_Prototype, which is composed of two subroutines named Method_Body & Excecution_Logic, to generate code from the combined model of activity and sequence diagrams consisting of concurrent activities. The authors compare the proposed method with other research outcomes with respect to workflow automation, support for concurrency, etc. The proposed algorithms are able to generate class definition, method definition and control flow. A case study is presented that demonstrates the algorithm, to generate Java code for the ATM operation.